Funding Gap in Hydropower Projects of Nepal: Does Internal Finance Matter? - Subedi, Kapil Deb (Saptagandaki Journal, 2018)
This paper aims to examine the current status of investment and availability of financing to hydro power companies in Nepal. Using pooled cross sectional data of NEPSE listed companies; a regression equation has been estimated to determine the effect of financing constraints on investment decisions of hydro companies. The study results confirm that internal cash flows and leverage are the major determinants of investment decisions in Nepalese hydro companies. Moreover, the coefficient of internal cash flow is significantly strong and positive showing its interdependency in financing new investment projects of hydro companies. This relationship strongly supports the financing constraints hypothesis that indicates the capital market frictions as the major obstacle of hydro investment in Nepal. Although the companies have access to banks and foreign capital, still the financing gaps persist and they are highly dependent on their internal cash flows for investment. Additionally, the volatility of cash flows and sales of hydro companies along with their long gestation period pose a significant credit risk to banks and lending institutions that hinder them to provide as much credit as they demand. Besides, the cyclical variations of net worth and collateral values of hydro companies during the tough economic period also resist them to obtain enough finance for further investment. Hence, the government should ensure with appropriate policies, information systems and regulatory mechanism that enable well functioning of capital markets to efficient flows of funds either in the form of equity or debt to boost up the hydropower investment in Nepal. The Sapta Gandaki Journal Vol. IX, 2018 Feb. Page: 34-52